Comparison of wind tunnel and on site measurements for urban wind energy estimation of potential yield. Issue 158 (November 2016) - Al-Quraan, Ayman; Stathopoulos, Ted; Pillay, Pragasen
Abstract: There is a need to compare wind tunnel results with field measurement wind data in order to examine the validity of wind tunnel data in providing realistic estimates of urban wind energy potential and assess the probable errors involved. The paper refers to and discusses two Montreal building cases with different upstream roughness homogeneity. In the first case, field wind speed measurements are used to calculate the wind energy potential for a building with upstream rather homogeneous suburban type of terrain. In the second case, the building upstream terrain is very rough and highly nonhomogeneous. The calculated wind energy potential based on the field measurements was compared with the estimated value based on respective boundary layer wind tunnel data. In the first case, where the upstream terrain is homogeneous, the difference between the estimation of wind energy potential and the calculation using the field measurements is less than 5%. However, in the second case with the nonhomogeneous upstream terrain conditions, the difference between the estimation of the wind energy potential and the calculation using the field measurements is increased by up to 20%.